Psychological interventions can have a positive impact on the treatment of individuals with psoriasis (Research, Society and Development, 2025)
Psoriasis is a chronic condition that affects not only the skin, but also the mental health and quality of life of affected patients. Studies have shown the relevance of psychological interventions, such as Cognitive-Behavioral Therapy (CBT) and mindfulness practices, in managing the disease. This study aims to review the literature on the effectiveness of psychological interventions in the treatment of psoriasis, analyzing their impact on clinical symptoms and quality of life. A systematic review of the literature was carried out, including clinical trials, observational studies and meta-analyses. The sources were selected based on relevance and methodological rigor, focusing on outcomes related to mental health, dermatological manifestations and quality of life. The results indicate that psychological interventions, especially CBT and mindfulness, are effective in reducing stress, anxiety and depression, as well as promoting improvements in the perception of the severity of psoriasis and in patients' quality of life and in the way they themselves perceive the severity of psoriasis, regardless of medical assessment. Limitations include the heterogeneity of research methods and the variation in evaluation criteria, which makes it difficult to generalize the results. Most studies have small sample sizes and short follow-ups. The integration of psychological interventions in the treatment of psoriasis is important for a holistic management of the condition, highlighting the importance of addressing both the physical and emotional aspects of the disease.